Framing Terrorism and Reputation of Security Forces in the KKB Case in Papua - Eldoris, Gustaaf Verian; Aisyah, Vinisa Nurul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: The aim of this research is to find out how detik.com and tempo.co frame the Papua KKB terrorism case and the reputation of the security forces. This study uses Robert N. Entman's Framing theory to find out a reality highlighted by the media and image restoration theory to see the reputation of security forces in media coverage. Methodology: The research method uses qualitative approach with framing analysis using four segments, namely defining problem, diagnosing cause, making moral judgment, and treatment recommendation. Results : The results of the study found that Detik.com and Tempo.co had differences in the framing of the Papua KKB news, where Detik.com highlighted acts of violence and terrorism while Tempo.co showed the actions of the security forces in forming a safe image for residents around the crime scene.